Cost-effectiveness of adjunctive negative pressure wound therapy in paediatric burn care: evidence from the SONATA in C randomised controlled trial - Cody C. Frear (Nature Portfolio, 2021)
Abstract Negative pressure wound therapy (NPWT) has been shown to improve clinical outcomes for children with burns by accelerating wound re-epithelialisation. Its effects on healthcare costs, however, remain poorly understood. The aim of this study was to evaluate the cost-effectiveness of NPWT from a healthcare provider perspective using evidence from the SONATA in C randomised controlled trial, in which 101 children with small-area burns were allocated to either standard care (silver-impregnated dressings) or standard care in combination with adjunctive NPWT. The primary outcome, time to re-epithelialisation, was assessed through a blinded photographic review. Resource usage and costs were prospectively recorded for each participant for up to 6 months. Incremental cost-effectiveness ratios and dominance probabilities were estimated and uncertainty quantified using bootstrap resampling. Mean costs per participant—including dressings, labour, medication, scar management, and theatre operations—were lower in the NPWT group (AUD $903.69) relative to the control group (AUD $1669.01). There was an 89% probability that NPWT was dominant, yielding both faster re-epithelialisation and lower overall costs. Findings remained robust to sensitivity analyses employing alternative theatre costs and time-to-re-epithelialisation estimates for grafted patients. In conclusion, adjunctive NPWT is likely to be a cost-effective and dominant treatment for small-area paediatric burns (ANZCTR.org.au:ACTRN12618000256279).